Strategies for Air‐Stable and Tunable Monolayer MoS2‐Based Hybrid Photodetectors with High Performance by Regulating the Fully Inorganic Trihalide Perovskite Nanocrystals. Issue 11 (18th March 2019) - Zhang, Louwen; Shen, Shaoli; Li, Man; Li, Luying; Zhang, Jibin; Fan, Lianwei; Cheng, Feng; Li, Chen; Zhu, Meng; Kang, Zhe; Su, Jun; Zhai, Tianyou; et al.
Abstract: The past several years have seen the rapid development of fully inorganic trihalide perovskite nanocrystals (PNCs) in the field of hybrid optoelectronic devices due to their outstanding photophysical properties and environmental stability. In this study, novel and easily implementable strategies are proposed to regulate the photoresponse performance of monolayer MoS2 /PNC hybrid photodetectors (HPs) without the photogating effect. The optoelectronic properties of these HPs are tuned by regulating the characteristic factors of colloidal PNCs (solution concentration and surface ligand content), which are closely associated with the light‐trapping ability of the perovskite layer and charge transfer efficiency at the heterojunction interface. Moreover, oxygen adsorbates are found to exhibit a typical p‐type behavior and play a decisive role in the improvement of response rate of the HPs. In the air, the HPs present a high photoresponsivity of 6.40 × 10 5 mA W −1, an external quantum efficiency of 1.50 × 10 5 %, and a specific detectivity of 3.38 × 10 11 Jones when the gate voltage is zero. The HPs also exhibit excellent thermal stability and operation durability, largely due to the intrinsic stability of PNCs. The present work provides promising strategies for regulating/optimizing the performance of advanced functional devices with mixed‐dimensional heterojunctions. Abstract : The performance of photodetectors is usually tuned by regulating the operating conditions. Here, novel and easily implementable strategies for the performance regulation without the photogating effect are successfully applied to the hybrid monolayer MoS2 /perovskite nanocrystal (PNC) photodetectors. The influence of oxygen adsorbates on the response process of the hybrid devices, as well as device stability, is also demonstrated.